The Influence of Market Orientation, Entrepreneurial Orientation, and Product Innovation on MSME Performance through Competitive Advantage in Culinary MSMEs in Kemiling, Bandar Lampung - Rosda Hayati; Euis Mufahamah; Amril Samosir (Yayasan Multidimensi Kreatif, 2026)
This study aims to investigate the influence of Market Orientation (MO), Entrepreneurial Orientation (EO), and Product Innovation (PI) on MSME Performance through the mediating role of Competitive Advantage (CA) within the culinary sector in Kemiling District, Bandar Lampung. Employing a quantitative approach grounded in the Resource-Based View (RBV) theory, data were collected via structured questionnaires from 136 owners and managers of culinary MSMEs using a purposive sampling technique. The data were analyzed using multiple linear regression and causal step mediation analysis via SPSS 23. The results reveal that Market Orientation and Entrepreneurial Orientation significantly and positively affect Competitive Advantage, whereas Product Innovation does not. Furthermore, all three independent variables directly and significantly enhance MSME Performance. The mediation analysis demonstrates that Competitive Advantage acts as a full mediator for Market Orientation and a partial mediator for Entrepreneurial Orientation. However, Product Innovation affects MSME performance directly without mediation by competitive advantage. This research extends the RBV literature by clarifying that competitive advantage is not a universal mediator; while it is essential for translating market intelligence into financial success, product innovation in a saturated local culinary market acts primarily as a direct short-term performance driver.